Frequency analysis of photoplethysmogram and its derivatives. Issue 3 (December 2015) - Elgendi, Mohamed; Fletcher, Richard R.; Norton, Ian; Brearley, Matt; Abbott, Derek; Lovell, Nigel H.; Schuurmans, Dale
Abstract: There are a limited number of studies on heat stress dynamics during exercise using the photoplethysmogram (PPG). We investigate the PPG signal and its derivatives for heat stress assessment using Welch (non-parametric) and autoregressive (parametric) spectral estimation methods. The preliminary results of this study indicate that applying the first and second derivatives to PPG waveforms is useful for determining heat stress level using 20-s recordings. Interestingly, Welch's and Yule–Walker's methods in agreement that the second derivative is an improved detector for heat stress. In fact, both spectral estimation methods showed a clear separation in the frequency domain between measurements before and after simulated heat-stress induction when the second derivative is applied. Moreover, the results demonstrate superior performance of the Welch's method over the Yule–Walker's method in separating before and after the three simulated heat-stress inductions.